30 Doradus, the double stellar birth scenario by N-body & warpfield clouds - Dominguez, Raul; Pellegrini, Eric William; Klessen, Ralf S.; Rahner, Daniel (Arxiv, 2022)
We study the evolution of embedded star clusters as possible progenitors to reproduce 30 Doradus, specifically the compact star cluster known as R136 and its surrounding stellar family, which is believed to be part of an earlier star formation event. We employ the high-precision stellar dynamics code NBODY6++GPU to calculate the dynamics of the stars embedded in different evolving molecular clouds modelled by the 1D cloud/clusters evolution code WARPFIELD. We explore clouds with initial masses of $M_\text{cloud}=3.16 × 10^{5}$ M$_\odot$ that (re)-collapse allowing for the birth of a second generation of stars. We explore different star formation efficiencies in order to find the best set of parameters that can reproduce the observation measurements. Our best-fit models correspond to a first stellar generation with masses between $1.26 × 10^4$ - $2.85 × 10^4 $M$_\odot$ and for the second generation we find a ≈ 6.32× 10^4$ M$_\odot$. Our models can match the observed stellar ages, cloud shell radius, and the fact that the second generation of stars is more concentrated than the first one. This is found independently of the cluster starting initially with mass segregation or not. By comparing our results with recent observational measurements of the mass segregation and density profile of the central zone we find close agreement, and thus provide supporting evidence for a centrally focused (re)-collapse origin to the multiple ages.
Version 1 vom 12 Mai 2022, Version 2 vom 13 Mai 2022
Im Titel wird "Warpfield" groß geschrieben
Gesehen am 17.10.2022